2008
DOI: 10.2478/v10042-008-0025-4
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cells based immunotherapy of patient with chondrosarcoma--case report.

Abstract: Abstract:We present a case report of patient with intracranial chondrosarcoma and attempt to use vaccination of dendritic cells as the salvage therapy. To our knowledge, this is the first case report of DCs vaccination in the head and neck chondrosarcoma. Immunotherapy with allogeneic DCs stimulated with tumor cell lysates in this case was demonstrated to be feasible, safe and well tolerated. Unfortunately we did not observe any clinical or immune response during vaccination. CD4+ and CD8+ regulatory cells cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Loss of p16 protein expression was found to correlate with histological grade of central chondrosarcomas [64]. In dedifferentiated chondrosarcoma, mesenchymal, clear cell chondrosarcoma and periosteal chondrosarcoma, p16 aberrations were found to be common (85,70,95 and 50% of cases, respectively) [14,17]. One study [62 & ] reported that the pRb pathway is affected in 96% of the high-grade central chondrosarcomas, either by a decrease in the amount of CDKN2A/p16 (48%), an increase in the amount of CDK4 (55%) or expression of cyclin D1 (62%).…”
Section: Tumour Suppressor Pathways: Retinoblastoma and P53mentioning
confidence: 90%
See 1 more Smart Citation
“…Loss of p16 protein expression was found to correlate with histological grade of central chondrosarcomas [64]. In dedifferentiated chondrosarcoma, mesenchymal, clear cell chondrosarcoma and periosteal chondrosarcoma, p16 aberrations were found to be common (85,70,95 and 50% of cases, respectively) [14,17]. One study [62 & ] reported that the pRb pathway is affected in 96% of the high-grade central chondrosarcomas, either by a decrease in the amount of CDKN2A/p16 (48%), an increase in the amount of CDK4 (55%) or expression of cyclin D1 (62%).…”
Section: Tumour Suppressor Pathways: Retinoblastoma and P53mentioning
confidence: 90%
“…Specific CD8 þ T cells against these antigens were able to specifically lyse chondrosarcoma cell lines in vitro [81,83]. One study [85] reported a patient with an intracranial chondrosarcoma who received allogeneic dendritic cell vaccination stimulated with tumour cell lysate, without any clinical or immune response during vaccination. No T-cell-mediated immunotherapeutic trial against chondrosarcoma-associated targets for chondrosarcoma patients has been published or is ongoing at the moment.…”
Section: Immunotherapymentioning
confidence: 99%
“…CD4 + and CD8 + T regulatory cells could be responsible for the ineffectiveness of this particular immunotherapy [21].…”
Section: Dendritic Cell Immunotherapymentioning
confidence: 99%